Standardization of Stage-Wise Requirement of Nutrients in Banana Cv. Grande Naine (AAA) - T N Balamohan; J Auxilia; R Sudha (Journal of Horticultural Sciences, 2015)
A field trial was conducted during 2009-2010 at College Orchard, Horticultural College and Research Institute, Tamil Nadu Agricultural University, Coimbatore, to standardize stage-wise requirement of nutrients in banana cv. Grand Naine (AAA). Treatment T16 where application of 100% RDF (165:52.5:495g NPK plant-1) at 4 critical growth stages, i.e., 40:52.5:25, 30:0:35, 30:0:25 and 0:0:15% at the 3rd, 5th, 7th and 9thmonths after planting (MAP), respectively, recorded maximum plant height, pseudostem girth and leaf area index. Maximum bunch weight of 32.15kg was recorded in T16. Higher yield was attributed to more number of (i) hands per bunch, (ii) fingers per hand and (iii) per bunch, besides the higher average weight of the finger. Better quality fruits, with higher TSS, total sugars, low acidity and better sugar:acid blend, were obtained in T16. In treatment T16, where 100% RDF was applied, increased N, P, and K content were seen in the index leaf of the crop. Lower soil-available nutrients, viz., N, P, K, at the higher level of split-application at critical stages of the crop revealed, that, the nutrients applied were utilized efficiently. This was reflected in the better yield and quality obtained. Economics were worked out which indicated T16 as giving the highest cost:benefit ratio (1:3.97).